OTUD4 inhibits ferroptosis by stabilizing GPX4 and suppressing autophagic degradation to promote tumor progression - Jinglian Chen; Chengqing Huang; Jiale Mei; Qiuhua Lin; Wenbo Chen; Jiali Tang; Xinjie Wei; Caixia Mo; Yueyan Zhang; Qi Zeng; Xianwei Mo; Weizhong Tang; et al. (Cell Reports)
Summary: Ferroptosis, a regulated cell demise predicated on iron metabolism and lipid peroxidation, has increasingly become a focal point in oncological therapies. Nonetheless, its governance, particularly the role of deubiquitination, is not fully delineated. This investigation concentrates on the deubiquitinase OTUD4, scrutinizing its functional and molecular implications in ferroptosis within tumor cells. By engineering OTUD4 knockout cell lines via CRISPR-Cas9, we observed that these cells exhibit heightened sensitivity to ferroptosis inducers, augmenting ferroptotic cell death and robustly diminishing tumor growth both in vitro and in vivo. Mechanistically, OTUD4 not only sustains protein stability by directly deubiquitinating GPX4 but also impedes its degradation via RHEB-mediated autophagy, collectively stalling the ferroptosis pathway. In vivo assays substantiate that OTUD4 deletion, when combined with regorafenib, drastically reduces tumor proliferation, showcasing potent synergistic antitumor activity. This study pioneers the revelation of OTUD4’s bifunctional role in modulating ferroptosis through deubiquitination and autophagy, underscoring its potential as a therapeutic target in oncology.